2023
DOI: 10.1177/21674795231155592
|View full text |Cite
|
Sign up to set email alerts
|

Task and Social Determinants of Coaches’ Reports of Leader-Member Exchange

Abstract: Leader-member exchange theory (LMX) has proliferated as a framework for understanding coach-athlete interactions, as the exchanges of communicative resources greatly influence athletes’ sporting experiences. The current study uses coaches’ perceptions of task and social determinants of LMX to reveal comparative insights about forming low- and high-quality exchanges. Data collected from 380 coaches, spanning 14 different sports, at 160 high schools indicated that high-quality exchanges are solely determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…The literature has not yet identified a universally accepted gold standard for effective leadership styles [ 53 ]. In healthcare, effective leadership necessitates a manager with a robust leadership education and behavioral attributes capable of fostering strong interpersonal relationships [ 53 ] which significantly influence followers’ behavior [ 37 , 54 , 55 ], including behavior related to their autonomy [ 38 ], satisfaction [ 37 , 38 ], organizational commitment, and intention to stay [ 37 ], thereby creating better work contexts to motivate the nursing workforce [ 56 , 57 , 58 , 59 , 60 ]. Identified managerial behaviors crucial for fostering trust, as per the conceptual definition of trust [ 7 , 19 ], include active listening, fostering open discussions; encouraging employee involvement [ 9 , 60 , 61 ], respect [ 9 ], empathy and understanding [ 5 , 9 , 61 ], and personalized support; and acknowledging individuality [ 5 , 9 , 22 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has not yet identified a universally accepted gold standard for effective leadership styles [ 53 ]. In healthcare, effective leadership necessitates a manager with a robust leadership education and behavioral attributes capable of fostering strong interpersonal relationships [ 53 ] which significantly influence followers’ behavior [ 37 , 54 , 55 ], including behavior related to their autonomy [ 38 ], satisfaction [ 37 , 38 ], organizational commitment, and intention to stay [ 37 ], thereby creating better work contexts to motivate the nursing workforce [ 56 , 57 , 58 , 59 , 60 ]. Identified managerial behaviors crucial for fostering trust, as per the conceptual definition of trust [ 7 , 19 ], include active listening, fostering open discussions; encouraging employee involvement [ 9 , 60 , 61 ], respect [ 9 ], empathy and understanding [ 5 , 9 , 61 ], and personalized support; and acknowledging individuality [ 5 , 9 , 22 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selection process for nurse managers lacks standardization and does not consistently consider their levels of competencies or other relevant indicators [ 66 ]. A standardized policy for leader selection in healthcare organizations remains a topic of debate [ 54 , 67 ]. In addition, another significant issue is the departure of nurse managers from their roles.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical construct of the LMX-7 scale has been conceptualized over the years, with the model suggesting that leaders develop unique relationships with each employee, and the quality of this relationship influences various aspects of followers’ behavior and actions [ 60 ]. Despite some previous criticism, our study has confirmed the one-dimensionality of the LMX-7 scale and its psychometric properties, which supports the original theoretical construct [ 7 ].…”
Section: Discussionmentioning
confidence: 99%